Pengembangan Wirausaha Olahan Rumahan Cemilan Seker (Seblak Kering) di Kampung Bunut Babakan Desa Bangbayang - Bramantiyo Eko Putro; Siti Komalasari (Unri Conference Series: Community Engagement, 2021)
The pandemic caused a decline in performance from the demand side which ultimately had an impact on the supply side, namely termination of employment and the threat of default in credit payments. MSMEs in Bangbayang village also experienced a large decline in product sales. The average decline in sales of MSMEs in Bangbayang Village reached 51%. And operating profit of 51%. This resulted in a 69% decrease in capital. The purpose of this community service activity is to help SMEs in Bangshadow Village, especially MakaroniQue home-processed entrepreneurs by making new products to increase income. The method used in this activity is the lecture method and direct practice of making MakaroniQue business innovations. The implementation of the service has succeeded in developing a new product, namely dry seblak (SEKER). The program ran smoothly and received feedback as expected. The sale of new products shows potential business opportunities with increasing sales every week. Achievement in the manufacture of new products, sales increased by about 44 pcs compared to the initial sales which could only sell 20 pcs.